2020
DOI: 10.3389/fpls.2020.00022
|View full text |Cite|
|
Sign up to set email alerts
|

Plastome Evolution and Phylogeny of Orchidaceae, With 24 New Sequences

Abstract: In order to understand the evolution of the orchid plastome, we annotated and compared 124 complete plastomes of Orchidaceae representing all the major lineages in their structures, gene contents, gene rearrangements, and IR contractions/expansions. Fortytwo of these plastomes were generated from the corresponding author's laboratory, and 24 plastomes-including nine genera (Amitostigma, Bulbophyllum, Dactylorhiza, Dipodium, Galearis, Gymnadenia, Hetaeria, Oreorchis, and Sedirea)-are new in this study. All orch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
109
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(180 citation statements)
references
References 78 publications
22
109
4
1
Order By: Relevance
“…To construct the phylogeny tree and determine Coelogyne ’s systematic position, we ultimately chose 67, from 28 genera, out of 122 species in the Orchidaceae, for which the full cp genome sequencing had been accomplished and officially published in the database of the NCBI. The results showed that the main relationship was the same as other studies among Vanilloideae, Orchidoideae, and Epidendroideae [ 32 ]. Within Epidendroideae, the relationship among tribes was ultimately the same as other studies using chloroplast genome CDS (coding sequence) [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To construct the phylogeny tree and determine Coelogyne ’s systematic position, we ultimately chose 67, from 28 genera, out of 122 species in the Orchidaceae, for which the full cp genome sequencing had been accomplished and officially published in the database of the NCBI. The results showed that the main relationship was the same as other studies among Vanilloideae, Orchidoideae, and Epidendroideae [ 32 ]. Within Epidendroideae, the relationship among tribes was ultimately the same as other studies using chloroplast genome CDS (coding sequence) [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that the main relationship was the same as other studies among Vanilloideae, Orchidoideae, and Epidendroideae [ 32 ]. Within Epidendroideae, the relationship among tribes was ultimately the same as other studies using chloroplast genome CDS (coding sequence) [ 32 ]. These results showed that a systematic evolutionary relationship was robust using chloroplast genomes.…”
Section: Discussionsupporting
confidence: 83%
“…cemA encodes a chloroplast envelope membrane protein (Sasaki et al, 1993) and is inferred to indirectly influence CO 2 uptake in plastid (Rolland et al, 1997). In some non-photosynthetic orchids, cemA exists as pseudogene or is lost (Feng et al, 2016;Kim et al, 2020). infA is crucial for genetic information transmission that affects transcription of DNA into RNA and translation of RNA to protein; it is seen as a housekeeping gene (Schelkunov et al, 2015).…”
Section: Location Regionmentioning
confidence: 99%
“…The expansion or contraction of the inverted repeats have been shown to occur in multiple land plant lineages (Wicke et al, 2011;Jansen & Ruhlman, 2012;Zhu et al, 2016) and can often be specific to a few genera within a family (Guisinger et al, 2011;Dugas et al, 2015;Tian et al, 2018;Thode & Lohmann, 2019). In Asparagales IR expansions have been reported in multiple genera in Orchidaceae incorporating genes from the SSC up to and including ccsA (Kim et al, 2015(Kim et al, , 2020, and in Eustrephus latifolius, Asparagaceae (Kim, Kim & Kim, 2016), where the IR expanded to include ycf1.…”
Section: Discussionmentioning
confidence: 99%